Estratégias competitivas para a indústria da carne bovina do Estado do Rio Grande do Sul: Um estudo das tendências do mercado consumidor e produção - Kontz, Leonardo Betemps (Universidade do Vale do Rio dos Sinos, 2021)
The beef market has an important role in the Brazilian economy and, especially, in the economy of the State of Rio Grande do Sul. Brazil is considered the largest world exporter in the segment and the third largest place in terms of consumption. Rio Grande do Sul, on the other hand, has the highest per capita consumption of beef in the country, but its industry has been losing ground on the national and global scene. Thus, the objective of this thesis was to identify and propose possible competitive strategies, which could be adopted in the beef industry, based on activities already developed in livestock in the geographic and economic space of RS. The research method was the single case study. Among the results obtained, the lack of articulation between livestock and industry and the need to create mechanisms that connect livestock, industry and the entire production chain stand out. Faced with the challenges, the possible strategies listed are: creation of an identity of origin, development of a brand for the product, standardization of production, traceability and elements that value the differentiating attributes of beef produced in Rio Grande do Sul.
Keywords: Estratégia; Mercado da carne bovina; Consumo e produção; Strategy; Beef market; Consumption and production; ACCNPQ::Engenharias::Engenharia de Produção